Torbulok, Tadschikistan - Lindström, Gunvor (e-Forschungsberichte des DAI, 2017)
The excavations at Torbulok in the Southwest of Tajikistan put another sanctuary on the map of religious sites of the Hellenistic Far East. Until 2016 more than 550 square meters were excavated with a complex of several terraces, courtyards and smaller buildings. They are from three phases, which are according to the ceramic evidence of Hellenistic date (end of 4th to mid-2nd century BC). Of special significance for ancient Bactrian religion is a courtyard with seven miniature altars as well as water basins connected to a cult installation containing several votive gifts and offerings. The sanctuary in Torbulok was likely a rural shrine of regional importance, a type of sanctuary previously unknown in Hellenistic Bactria.